Learning to Solve Counting Problems: Challenges and Opportunities for Non-Math Majors - Orit Zaslavsky; Katherine V. Pauletti; Victoria Krupnik (Korea Society of Educational Studies in Mathematics, 2020)
Our study stems from the belief that meaningful and challenging mathematics can be made accessible to all students. To this end, we designed and implemented a special course for undergraduate non-mathematics and non-mathematics education majors. The course entitled Counting and Chance satisfied the requirement of a core course in quantitative reasoning. The content chosen as the focus of this course was basic combinatorics (i.e., counting problems) - a topic that is non-procedural in nature and could be made accessible to students with limited mathematical background. The design of the course was inspired by inclusive pedagogical principles that motivate and support students' conceptual learning. We present the characteristics of the learning environment that was developed within the framework of this course, point to the rich and sophisticated kinds of reasoning that students developed throughout the course, and discuss how students' collaborative engagement in the learning process seemed to have contributed to their views of themselves as math learners and their conceptions of what math is. Our findings point to the feasibility of such a course for non-math students, and its potential merit in helping students: (i) develop appreciation of mathematics as a topic that requires thinking, reasoning, and convincing; (ii) become more confident in their ability to do math.